Вплив видів міскантусу на структурні та морфологічні особливості отриманої мікрокристалічної целюлози - Tkachenko, T.V.; Haidai, O.O.; Korinenko, B.V.; Kamenskyh, D.S.; Baran, M.M.; Povazhny, V.A.; Starik, S.P.; Bohatyrenko, V.A.; Bratishko, V.V.; Yevdokymenko, V.O. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2026)
Miscanthus shows great potential for producing cellulosic materials due to its high yield and low cultivation requirements. This fast-growing perennial grass can serve as an alternative raw material, replacing traditional wood. Research conducted abroad has indicated that the original Miscanthus species affects the quality of the final product; however, similar studies on domestic varieties are lacking. Our study aimed to obtain microcrystalline cellulose (MCC) from different Miscanthus species, found their physicochemical characteristics, and compare them. We used air-dried Giant miscanthus (Miscanthus giganteus), Chinese miscanthus (Miscanthus sinensis), and Sugar miscanthus (Miscanthus sacchariflorus), which are considered technical crops. The composition of these species was as follows: cellulose content of 46.0, 44.8, and 42.2 %; hemicellulose content of 23.2, 28.3, and 27.2 %; lignin content of 14.2, 11.5, and 10.8 %; and ash content of 2.8, 4.1, and 6.7 %, respectively. To produce microcrystalline cellulose, the Miscanthus species underwent organo-solvent cooking. We studied the structure and morphology of the resulting MCC using various methods, including X-ray diffraction (XRD), X-ray fluorescence (XRF), Fourier-transform infrared spectroscopy with attenuated total reflectance (FTIR-ATR), and atomic force microscopy (AFM). The results indicated that MCC was successfully obtained from Giant miscanthus, Chinese miscanthus, and Sugar miscanthus, with yields of 95.9, 95.4, and 95.2 %, respectively, using the organo-solvent cooking method. The final product was a white, tasteless, and odourless substance with the following organic components: 95.8, 94.0, and 90.9 % (including 97.7, 96.4, and 97.8 % cellulose, as well as 2.3, 3.6, and 2.2 % lignin). The inorganic components accounted for 4.2, 6.0, and 9.1 % (including 96.1, 69.9, and 95.3 % SiO2, respectively). The XRD method confirmed the presence of a crystalline structure in the obtained MCC, with calculated crystallinity indexes of 0.73, 0.68, and 0.60. The FTIR-ATR spectra revealed typical functional groups associated with MCC and pure silicon dioxide at wavenumbers of 1148–1144, 901–898, and 450–414 cm–1. Furthermore, AFM analysis demonstrated that the particles were nanoscale in size. All MCC samples exhibited a striped texture characterised by nearly parallel and linear stripes. Notably, the MCC derived from Sugar miscanthus displayed a partially globular surface relief.